Assessing factors associated with discharge from opioid agonist therapy due to incarceration in the United States - Marotta, Phillip L. (J Addict Dis, 2019)
The following study investigates factors associated with discharge from OAT due to incarceration in a sample of 64,331 discharges in the United States. Multinomial regression investigated the association between demographic factors, prior arrest, referral source (i.e criminal justice agency) intravenous drug use, types of drug used, length of prior treatment and discharge due to incarceration compared to completing treatment or discharge due to other reasons. African Americans, Latinx, and Native Americans were at greater risk of discharge due to incarceration compared to whites. Referral to OAT from criminal justice agencies and self-referral was associated with increased risk of discharge from OAT due to incarceration compared to referral from a health care provider. Substance use of heroin, benzodiazepines, synthetic opioids, cocaine and non-prescription use of methadone were associated with discharge due to incarceration. Risk of discharge due to incarceration was higher for patients who reported intravenous drug use and who reported a co-morbid psychiatric problem. These findings enrich a nascent body of literature on mechanisms associated with attrition from OAT due to incarceration and emphasize the need for programs to divert people with OUD from incarceration to increase engagement and retention in OAT.